Electronic Structure and Optical Response of Zn‐Based Metal–Organic Frameworks. Issue 9 (26th June 2018) - Vrubel, Ivan I.; Senkevich, Natalia Yu.; Khramenkova, Elena V.; Polozkov, Roman G.; Shelykh, Ivan A.
Abstract: The results of theoretical investigation of the equilibrium spatial configuration, electronic structure, and optical properties of the Zn‐based metal–organic framework [Zn2 (TBAPy)(H2 O)2 *3.5DEF] n are reported. The electronic structure is obtained in frameworks of the density‐functional theory (DFT) with BLYP and PBE exchange‐correlation functionals, and optical response is computed using time‐dependent density functional theory (TDDFT). It is shown that the formation of narrow LUMO and HOMO bands is provided by conjugated π‐electrons of the aromatic rings of the ligand. These bands have nontrivial pattern and contain regions of hyperbolic dispersion corresponding to highly anisotropic heavy fermions. Optical transitions between these bands result in the appearance of near‐threshold peaks in photoabsorption spectra. The structure of the bands prevents formation of the bright exciton states in the system, and thus optical response is governed by single particle excitations only. Abstract : The electronic structure and optical response of Zn‐based metal‐organic frameworks (MOF‐Zn) in monolayer and bilayer configurations are investigated within the density functional theory approach. It is demonstrated that two narrow peaks in the density of states, corresponding to HOMO and LUMO orbitals, are formed near the edges of the conduction and the valence bands. The band structure of these states prevents formation of bright excitons in the system.